TINJAUAN YURIDIS TERHADAP PEMERIKSAAN BERITA ACARA SAKSI DALAM PERKARA PIDANA NARKOTIKA NOMOR:778/PID/B/2011/PN.PBR DI PENGADILAN NEGERI PEKANBARU. - Wahyu Rizqy Yusmanita; Mukhlis R; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Narcotics criminal case number : 778/PID/B/2011/PN.PBR in Pekanbaru District Court complaint originated from one society to Br . Mastur that the defendant often buy narcotics Category I ( one ) of dry marijuana , then witness Mastur and Rahmat Hasbi who is a member of the police directorate Riau regional police drug detectives raided the defendant's home and found 1 ( one ) package of dried marijuana leaves wrapped in newspaper and in inside is a 1 ( one ) package of dried marijuana leaves small . Based on the examination of the defendant be examined and investigated by the investigator and the Riau Police Narcotics Investigation Directorate , and was charged by the public prosecutor on charges of violating the provisions of Section 114 and punishable Paragraph ( 1 ) Jo Article 111 Paragraph ( 1 ) of Law No. 35 of 2009 on Narcotics . This case has also been examined and decided by the judges at the Court of Pekanbaru acquittal . In conducting this study the authors chose the subject matter , namely : How the BAP witnesses during the investigation that resulted in acquittal in the criminal case of pure narcotic Number : 778/PID/B/2011/PN.PBR and What accounts free judge in the case dropped this . The purpose of this thesis , namely ; First , the validity of the dossier Knowing witnesses that resulted in a verdict with narcotics criminal case number : 778/PID/B/2011/PN.PBR , Second , Knowing the judge's decision is based on consideration of the minutes of the examination of witnesses in criminal case narcotics Number: 778 / PID/B/2011/PN.PBR .The method used in this study were classified its kind when viewed from the normative legal research. While the data used consisted of secondary data including primary legal materials and secondary legal materials and legal materials tertiary.The results of the study are: Making minutes of examination of witnesses on narcotics criminal case number: 778/PIB/B/2011/PN.PBR not conducted in accordance with the laws that govern them because they do not meet the elements of material and formal elements of a investigation report. investigation report that was not accepted by the judges as evidence that this is considered to be one of the judges in decisions independent of the defendant and the panel of judges at the district court in Pekanbaru into consideration as follows: